Behind the front page a candid look at how the news is made - Broder, David S. (Simon and Schuster, 1987)
With almost 30 years experience as a political correspondent, David Broder, a Pulitzer Prize-winning journalist for The Washington Post, takes us inside the newsroom and on the beats to show how reporters do their jobs. Covering every president from Eisenhower to Reagan, he examines the press-president relationship from Kennedy's near camaraderie to Nixon's open mistrust to Reagan's approach. He describes how a reporter gets his story, with examples such as Woodward and Bernstein's Watergate sources. He explains press successes and failures, and also examines ethical issues -- when to publish, when not to.